2017
DOI: 10.1016/j.bbi.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation and resting state connectivity of the default mode network

Abstract: The default mode network (DMN) encompasses brain systems that exhibit coherent neural activity at rest. DMN brain systems have been implicated in diverse social, cognitive, and affective processes, as well as risk for forms of dementia and psychiatric disorders that associate with systemic inflammation. Areas of the anterior cingulate cortex (ACC) and surrounding medial prefrontal cortex (mPFC) within the DMN have been implicated specifically in regulating autonomic and neuroendocrine processes that relate to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 84 publications
4
65
0
Order By: Relevance
“…This is consistent with the previous finding which reported that psychosocial stress may alter functional connectivity of the insula and anterior cingulate, both of which were associated with increased levels of IL-6 and TNF-α 30 . Considering that IL-6 has shown to associate with the functional connectivity within the DMN 34 , the current findings may further support that the connectivity among the triple-network model may act as neural correlates of PTS symptoms in combination with lowgrade inflammation. In addition, growing evidence suggests that the insular cortex, a key node of the SAN, and its functional link to other brain regions play a crucial role in the central representation of inflammation [35][36][37] as well as anxiety or depression 36,38 .…”
Section: Discussionsupporting
confidence: 64%
“…This is consistent with the previous finding which reported that psychosocial stress may alter functional connectivity of the insula and anterior cingulate, both of which were associated with increased levels of IL-6 and TNF-α 30 . Considering that IL-6 has shown to associate with the functional connectivity within the DMN 34 , the current findings may further support that the connectivity among the triple-network model may act as neural correlates of PTS symptoms in combination with lowgrade inflammation. In addition, growing evidence suggests that the insular cortex, a key node of the SAN, and its functional link to other brain regions play a crucial role in the central representation of inflammation [35][36][37] as well as anxiety or depression 36,38 .…”
Section: Discussionsupporting
confidence: 64%
“…Thus far, only three resting state fMRI studies have addressed changes in functional connectivity associated with inflammatory markers (Labrenz et al, 2016;Lekander et al, 2016;Marsland et al, 2017), but none of them addressed the putative role of the salience network in anxiety. We now document a decrease in functional connectivity between nodes of the salience network and amygdala during inflammation, including reduced connectivity between amygdala and anterior insula.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in resting state brain activity have been shown to predict several psychiatric conditions including depression, schizophrenia and autism (Broyd et al, 2009), but received only little attention in the context of clinical or experimental anxiety. So far, only three fMRI studies documented effects of experimentally-induced systemic inflammation on resting state activity in healthy humans (Labrenz et al, 2016;Lekander et al, 2016;Marsland et al, 2017). These studies, including the one from our research group (Labrenz et al, 2016) however, did not investigate psychological components of the sickness response like anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, aspects of systemic physiology that have been linked to CVD risk and discrimination have been separately linked to activity patterns in these networks. [143][144][145] Relationship between neural systems and CVD risk. Neural activity in the brain system discussed by Gianaros and Wager 67 and Muscatell and Eisenberger 68 is associated with CVD risk.…”
Section: Neuralmentioning
confidence: 99%